1986
DOI: 10.1128/jcm.24.3.431-434.1986
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial comparing bacitracin with Strep-A-Chek for accuracy and turnaround time in the presumptive identification of Streptococcus pyogenes

Abstract: In a clinical trial, Strep-A-Chek (a 10-min chromogenic test) was compared with the bacitracin disk susceptibility test for accuracy and turnaround time in the presumptive identification of Streptococcus pyogenes. Among 461 isolates of beta-hemolytic streptococci (344 throat isolates and 117 isolates from other sites), 303 group A S. pyogenes isolates were found. The sensitivities of the Strep-A-Chek and bacitracin tests were high (96.4 and 100%, respectively), but the bacitracin test had a lower specificity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The Strep-A-Chek results were comparable to those previously reported (5). Although this method offers the advantage of rapid positive results (<10 min), the color developer provided in the kit is unstable, must be reconstituted for each test or batch of five tests, and used within 30 min of reconstitution.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…The Strep-A-Chek results were comparable to those previously reported (5). Although this method offers the advantage of rapid positive results (<10 min), the color developer provided in the kit is unstable, must be reconstituted for each test or batch of five tests, and used within 30 min of reconstitution.…”
supporting
confidence: 81%
“…and others (3,4) have demonstrated that L-pyrrolidonyl-pnaphthylamide (PYR) hydrolysis is a reliable test for the identification of GAS and ENT. Whereas earlier tests required incubation for 4 h to overnight to obtain results, recent modifications allow detection of PYR hydrolysis in 10 to 15 min (1,4,5). This study describes two PYR tests.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For cultures with no isolated colonies, subculture and subsequent direct plate testing offer an easier method than testing from broth culture. In the present study, 59.8% of all primary isolation cultures yielded colonies that could be tested as others have reported (1,9). Because of the design of the study, only six cultures had too few isolated colonies to be tested from primary culture.…”
Section: Discussionmentioning
confidence: 52%
“…In most cases, the test can be interpreted after overnight incubation. A disk test for determining the presence of pyrrolidonylarylamidase (PYRase) has been previously described for the identification of group A streptococci as well as enterococci (6,8,17). We have previously described a vancomycin susceptibility (Van s ) screening test to aid in the identification of viridans group streptococci (4).…”
mentioning
confidence: 99%